Terrorism and national security reform : how commissions can drive change during crises - Tama, Jordan , 1976- (Cambridge University Press, 2011)
"Terrorism and National Security Reform demonstrates that blue-ribbon commissions can be powerful vehicles for policy change, overturning the conventional wisdom that views them only as devices for passing the buck. Jordan Tama explains how the unique political credibility of commissions can enable them to forge bipartisan consensus on tough policy challenges. He also shows that commissions are most valuable during a crisis, when policymakers face pressure to make changes but frequently cannot agree on what to do. Using an original database, case studies, and more than 200 interviews of policymakers and commission participants, Tama reveals how commissions have shaped Barack Obama's plan for ending the Iraq War, spurred the largest government and intelligence overhauls since 1947, and driven many other elements of U.S. counterterrorism policy. In an era of unrelenting partisanship and extreme polarization, this book shows that commissions are increasingly valuable policymaking tools"